2018
DOI: 10.1007/s12011-018-1600-y
|View full text |Cite
|
Sign up to set email alerts
|

Tissue Concentrations of Zinc, Iron, Copper, and Magnesium During the Phases of Full Thickness Wound Healing in a Rodent Model

Abstract: Wound healing is a complex orchestration of processes involving cell proliferation, migration, differentiation, anabolism, and catabolism in order to restore skin continuity. Within these processes, elements such as metallic ions are involved due to their implications in cell behavior and enzymatic activity regulation. This study analyzed the kinetics of zinc, iron, copper and magnesium concentrations in a full thickness open wound rat model over 14 days. We made wounds with a diameter of 6 mm on the back of L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
68
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(70 citation statements)
references
References 31 publications
2
68
0
Order By: Relevance
“…While the content of zinc in the plant material was not sufficient to grant the recommended dietary allowances [49], it may likely contribute to wound healing when applied locally, as it has been found that the amount of zinc in the wound increases during the healing process. This may induce the keratinocyte proliferation, as it has been shown that keratinocyte proliferation and differentiation are controlled by zinc [50].…”
Section: Metal Contents In E Purpurea Aerial Partsmentioning
confidence: 99%
“…While the content of zinc in the plant material was not sufficient to grant the recommended dietary allowances [49], it may likely contribute to wound healing when applied locally, as it has been found that the amount of zinc in the wound increases during the healing process. This may induce the keratinocyte proliferation, as it has been shown that keratinocyte proliferation and differentiation are controlled by zinc [50].…”
Section: Metal Contents In E Purpurea Aerial Partsmentioning
confidence: 99%
“…2h, the concentration of Cu ions released from the NMHK and NMPGA was also analyzed. Similar to the release of NO, the release of Cu ions was also slower in NMPGA when compared with that in NMHK, which would accelerate the healing process [41][42][43]. Thus, the release results demonstrated that NMPGA could provide a suitable microenvironment for tissue regeneration by controlling the release rate of NO and Cu ions.…”
Section: Characterization Of Nmhk and Nmpgamentioning
confidence: 85%
“…Its microbiome and its physical, chemical, and immune barriers constitute an interactive network that protects individuals from external harm [ 21 ]. The 5 elements tested in the current study strongly influence the functions of skin, with effects on wound healing [ 22 , 23 ], scar formation and contraction [ 24 ], microvasculature blood flow [ 25 , 26 ], and immune function [ 27 ]. A deficiency of these 5 elements may cause skin lesions [ 28 – 30 ], while supplementation may lead to improved skin functions [ 21 , 31 ].…”
Section: Discussionmentioning
confidence: 99%